Total factor productivity in South African manufacturing firms - Friedrich Kreuser; Carol Newman (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
The manufacturing sector is an important source of productivity growth and exports. Manufacturing firms are generally more productive than firms in the agricultural or services sectors and are an important source of job creation. Little is known about the productivity performance of the sector and its drivers in South Africa. The recent availability of firm-level tax administration data has made it possible to measure and analyse the productivity of manufacturing firms in South Africa for the first time. In this paper, we use firm-level data for the period 2010-13 to estimate total factor productivity in the South African manufacturing sector. We examine differences in the level and growth of productivity across manufacturing sub-sectors and examine the heterogeneity in productivity levels within sectors. Our analysis paves the way for future research into the factors driving productivity growth of manufacturing firms that will contribute to the evidence base of the reasons for the significant heterogeneity in measured firm performance, even within narrowly defined sectors and size groups.
Keywords: D22; D24; O12; 330; total factor productivity; South Africa; heterogeneity; tax administration data